Surgery and Platinum/Etoposide-Based Chemotherapy for the Treatment of Epithelioid Trophoblastic Tumor. Issue 6 (1st June 2018) - Sobecki-Rausch, Janelle; Winder, Abigail; Maniar, Kruti P.; Hoekstra, Anna V.; Berry, Emily; Novak, Karen; Lurain, John R.
Abstract : Objective: Epithelioid trophoblastic tumor (ETT) is a rare variant of gestational trophoblastic neoplasia that develops from chorionic-type intermediate trophoblast, simulates carcinoma, presents years after a pregnancy event, is associated with low or normal human chorionic gonadotropin levels, and is relatively resistant to chemotherapy. Our aim was to identify the role of surgery in combination with platinum/etoposide-based chemotherapy in the management of both localized and metastatic ETT. Methods: A retrospective review was performed of women with ETT treated at a gestational trophoblastic disease center from 2010 to 2016. Results: Five patients were identified who had complete records. Mean age was 38.0 years. Three women presented with abnormal uterine bleeding, 2 women presented with respiratory complaints, and 1 woman was asymptomatic. Two women had no identifiable antecedent pregnancy, 2 women had spontaneous abortions, and 1 woman had a normal term delivery before diagnosis. Four (80%) of 5 women had metastatic pulmonary disease. All 5 women underwent hysterectomy, and 3 women had resection of metastatic pulmonary disease. The 4 women with metastatic disease were also treated with chemotherapy. All 5 women are currently without evidence of disease. Conclusions: Surgery, including hysterectomy and resection of metastatic disease, is an important component in the treatment of women with ETT. Adjuvant chemotherapy with a platinum/etoposide-containing regimen should be used in women with metastatic disease. All 5 women with ETT in this series were cured using this approach, including the 4 who had metastatic disease.